Homogenization of thermomechanical tread‐road contact for the investigation of tire rolling resistance. Issue 1 (25th October 2016) - Beyer, Robert; Nackenhorst, Udo
Abstract: A homogenization framework for the stochastic average meso‐scale tread‐road interaction with emphasis on macro‐scale rolling resistance calculations is presented in this contribution. This framework accounts for large scale, high‐frequency penetration of tread rubber by the highest asperities as well as for the nonlinear thermo‐viscoelastic material behavior of this tread rubber in the regime of finite strains. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)